2000
DOI: 10.4049/jimmunol.165.3.1673
|View full text |Cite
|
Sign up to set email alerts
|

Linkage Analysis of Systemic Lupus Erythematosus Induced in Diabetes-Prone Nonobese Diabetic Mice byMycobacterium bovis

Abstract: Systemic lupus erythematosus induced by Mycobacterium bovis in diabetes-prone nonobese diabetic mice was mapped in a backcross to the BALB/c strain. The subphenotypes—hemolytic anemia, antinuclear autoantibodies, and glomerular immune complex deposition—did not cosegregate, and linkage analysis for each trait was performed independently. Hemolytic anemia mapped to two loci: Bah1 at the MHC on chromosome 17 and Bah2 on distal chromosome 16. Antinuclear autoantibodies mapped to three loci: Bana1 at the MHC on ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
43
0

Year Published

2001
2001
2011
2011

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 39 publications
(43 citation statements)
references
References 81 publications
0
43
0
Order By: Relevance
“…Without knowing what microbial species are protective, what expressed constituents are responsible for this activity, or how their presence is recognized by the immune system, attempts to establish immunotherapies based on manipulating microbial exposure are fraught with danger. For example, the proposed use of bacillus Calmette-Guérin to treat MS (8) and diabetes (9) was associated with the precipitation of a lupus-like disease in mice (10)(11)(12).…”
Section: Ultiple Sclerosis (Ms) Is a Complex Genetic Traitmentioning
confidence: 99%
“…Without knowing what microbial species are protective, what expressed constituents are responsible for this activity, or how their presence is recognized by the immune system, attempts to establish immunotherapies based on manipulating microbial exposure are fraught with danger. For example, the proposed use of bacillus Calmette-Guérin to treat MS (8) and diabetes (9) was associated with the precipitation of a lupus-like disease in mice (10)(11)(12).…”
Section: Ultiple Sclerosis (Ms) Is a Complex Genetic Traitmentioning
confidence: 99%
“…One reason for this is that most of the major autoimmune diseases, including type I diabetes mellitus (DM) 3 and systemic lupus erythematosus (SLE), have polygenic origins (1)(2)(3). Linkage analysis and genetic mapping studies in murine models of these two diseases suggest that as many as 20 genes contribute to the development of type I DM in mice (2), while as many as 30 genes contribute to the development of SLE (3). Elucidating the genetic origins of autoimmunity is further complicated by the fact that diseases such as SLE almost certainly represent syndromes, with multiple different underlying genetic abnormalities or environmental factors leading to a common final phenotype.…”
mentioning
confidence: 99%
“…However, other QTL that map to the 80-90 Mbp chromosome 4 interval include loci that control the immune response (Ifa and Ifb), splenomegaly (Sbw2, Orgwg6 and Spm1), and anti-red blood cell IgG antibodies (Arigg3), which have been implicated in mouse models of autoimmune haemolytic anaemia and systemic lupus erythrematosus [7][8][9]. Significantly, a mouse anti-erythrocyte autoantibody modifier locus (Aem3) and anti-nuclear autoantibody locus (Bana2) co-localise to the suggestive E/NE bone marrow cell ratio QTL on chromosome 10, and a human haematocrit level QTL has also been mapped to chromosome 6q23-24, syntenic to mouse chromosome 10 QTL [1].…”
Section: Discussionmentioning
confidence: 99%
“…For example, QTL that are linked to anti-red blood cell and antinuclear antibody production and splenomegaly have been mapped in mouse models of AHA and SLE [7][8][9]. Similarly, QTL have been identified that determine mouse stem, progenitor and mature white blood cell numbers [10][11][12][13][14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%